Investigations on the Performance Comparison of Co-Prime Array with and without interpolation for DOA Estimation - ch, Lokesh Dharma Theja; Puli, Kishore Kumar (IRO Journal on Sustainable Wireless Systems, 2023)
The sparse arrays have recently attracted a lot of attention in the last decade, due to their ability to find more sources than sensors present in an array configuration. There might be some sparse arrays which might have holes in their difference coarray, and different interpolation techniques are used to fill these holes. In this paper, the comparison of estimation performances using RMSE vs SNR plots of co-prime array before and after interpolation are analyzed using both coarray MUSIC and ESPRIT algorithms.